A permanência do jovem no campo: uma análise para o Sudoeste do Paraná - Miecoanski, Flávia Regina (2018)
The family farm, characterized mainly by labor and farm management, presents an important economic activity in the southwestern Paraná. In this way, it is important ascertain the future this activity, that theoretically, depend of young people that are children of these families farm. The objective this essay was to verify which the factors that influence the permanence or the output of the young person in the rural area. To attend the objective propose was realized an interview with students of 3rd year of technical course in farming of State Center for Professional Education in the Southwest of Paraná, localized at Francisco Beltrão/PR. The sample, composite by 52 young people, was taken not random order, of now that had to attend necessary requirements, as be child of family farm and reside in rural area. The application form, only tool of data collection, was submitted the validation and count on the contribution of eight professionals that work with the theme. The results show that the main factors that influence of young person to permanence or output in the rural area are the farm size, mechanization of properties, conversation with parents and the participation in decision-making in the property, and the options of leisure in the rural area.